Methylammonium lead bromide based planar perovskite solar cells using various electron transport layers. (June 2021) - Jeyakumar, R.; Bag, Atanu
Highlights: Seven different electron transport layers are used in the solar cell. An ideal metal work function was found for Ohmic contact with transport layers. Energy band structure analyzed for the cell containing various electron transport layers. Using contour map, required thickness was found for various electron transport layers. High open-circuit voltage solar cell designed. Abstract: Methylammonium lead bromide (MAPbBr3 ) perovskite is a suitable absorber material for high open-circuit voltage (Voc ) solar cell due to its wide band gap. In this work, the impact of MAPbBr3 thickness, energy band structure, top and bottom electrode work functions on Voc, short circuit current density (Jsc ), fill factor, and cell efficiency has been studied in detail for various electron transport layers (ETLs) used independently in the device. The influence of top and bottom electrode work functions on internal quantum efficiency (IQE) has been investigated for the cell containing various ETLs. Our result shows that CdSe and PCBM are not suitable ETLs for MAPbBr3 based solar cells since shallow valence band maximum (VBM) of CdSe and PCBM at the absorber/ETL interface enhances recombination leading to a low Voc and cell efficiency. However, maximum power rectangle is obtained when PCBM used as ETL which can be attributed to less series resistance. For high performing device, top electrode work function between −4.0 and −4.4 eV is required for Ohmic contact. Bottom electrode work function ranging from −4.9 eV to −5.26 eV is required for Ohmic contact with spiro-OMeTAD as hole-transport layer (HTL). IQE gradually enhanced when the top (bottom) electrode work function is varied from −4.85 eV to −4.0 eV (−4.1 eV to −5.26 eV) showing an improvement in collection efficiency and contact at the electrode interface. A high Voc of 2.15 V, Jsc of 9.5 mA/cm 2, fill factor of 0.9 and an efficiency of 18.5% were obtained when TiO2 is used.